Pengaruh Human Capital Terhadap Kinerja Karyawan Unit Simpan Pinjam Koperasi Serba Usaha (Ksu) Mekar Surya Karanganyar - Triatmaja, Doddy Wahyu; , Kussudiyarsana S.E., M.Si (2016)
The purpose of this research was to examine the effect of the level of education, skills and work experience to the performance on employee savings and loan koprasi all-round effort (KSU) solar bloom karanganyar 2016. The sample used in employee savings and loan koprasi all-round effort (KSU) solar bloom karanganyar 2016 with the number of 39 respondents. Analyzer used to test the validity, reliability test, classic assumption test, multiple linear regression, t-test, F and determinant coefficient. These results were processed using SPSS software. The results obtained are at variable levels of education, skills and work experience have a significant effect on employee performance. This is evidenced by sig. education level 0.006, sig. skills and work experience 0,001 0,026 smaller than 0.05. F test value sig. 0.00024 smaller than 0.05 so that the variable level of education, skills and work experience simultaneously significant effect on the performance of employees in the Savings and Loans Unit Business Multipurpose Cooperative (KSU) Surya Mekar Karanganyar. From the results of this study contribute to achieve the level of education, skills and work experience on the performance of employees by 74% and the rest influenced by another factor of 26%.